(untitled) - Jianjun, Jin (Phillippines, 2017)
This is repost introduce about valuing health risk in agriculture a choice experiment approach to pesticides in Anqiu county, China
Keywords: Nông nghiệp,Agriculture; Khía cạnh môi trường,Environmental aspects